PENGARUH TEKNIK AUDIT BERBANTUAN KOMPUTER, KOMPETENSI AUDITOR, INDEPENDENSI, DAN PENGALAMAN KERJA TERHADAP KUALITAS AUDIT (STUDI PADA AUDITOR BPK RI PERWAKILAN PROVINSI ACEH) - Muhayoca, Risky; Ariani, Nita Erika (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2017)
The results of such audit examination by the BPK audit findings demonstrate the ability of auditors to detect errors contained in the financial statements that shows the good quality of the audit. This study aims to determine the effect of Computer Assisted Audit Technique, Auditor Competence, Independence, and Work Experience on Audit Quality. The data used in this study is the primary data by spreading the questionnaire on all BPK RI auditors Aceh Province Representative. The population in this study were all auditors at the office of BPK-RI Aceh representative.The process of collecting data and information needed in this research is done by field research (field research). The data used are primary data obtained directly from research subject in the form of questionnaire. The influence of independent variable to dependent variable is done by using multiple regression model.The results showed that both partially and collectively, computer-assisted audit techniques, auditor competence, independence, and work experience had an effect on audit quality on auditor BPK RI Representative of Aceh Province